The Palgrave Handbook of Workers' Participation at Plant Level - Berger, Stefan; Pries, Ludger; Wannöffel, Manfred (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2019)
Comprising the study, documentation, and comparison of plant-level workers' participation around the world, this volume meets the challenge of offering a global perspective on workers' participation, representation, and models of social partnership. Value chains, economic life, inter-cultural exchange and knowledge, as well as the mobility of persons and ideas increasingly cross the borders of nation-states. In the knowledge age, the active participation of workers in organizations is crucially important for sustainable and long-term growth and innovation. This handbook offers lessons from historical, global accounts of workers' participation at plant level, even as it looks forward to predict forthcoming trends in participation.